Skinner and Rosanvallon: Reconciling the History of Political Thought with Political Philosophy - Hörcher, Ferenc (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2015)
This paper addresses the issue of whether a proper history of political thought should avoid any contact with substantive political philosophy, as it was vehemently claimed earlier by Cambridge historians of political thought, or not. It argues that (A) a strong political or philosophical bias might kill the credibility of a reliable history of political thought, but (B), in this genre, it is by definition impossible to avoid taking on board politico-philosophical concerns. What is more, the paper also tries to show (C) the relevance of political philosophy for the history of political thought and vice versa. In particular, it will argue along the following two lines: (a) Without a political philosophical self-positioning any reconstruction of the history of political thought remains underdetermined and therefore uninstructive, and (b) without a look at the history of political thought political philosophy remains blind, alienated, theoretically unfounded and therefore potentially even dangerous. Methodologically, the paper aims to recapture some of the conclusions of the debates of the relationship of the two disciplines, with special attention to the French and British contexts (more particularly to the oeuvres of Rosanvallon and Skinner).

Artykuł podejmuje zagadnienie czy właściwa historia myśli politycznej powinna wystrzegać się wszelkiego kontaktu z poważną filozofią polityczną, którego to stanowiska żarliwie bronili wcześniej historycy myśli politycznej z Cambridge, czy też nie. Przedstawiono tu pogląd, że silna stronniczość w dziedzinie polityki czy filozofii może zniszczyć wiarygodność miarodajnej historii myśli politycznej, ale uprawiając tę naukę z definicji nie sposób uchronić się przed rozważaniami polityczno-filozoficznymi. Artykuł próbuje także wykazać związek filozofii politycznej z historią myśli politycznej i vice versa. Artykuł szczególnie koncentruje się na następujących dwóch twierdzeniach: a) wszelka rekonstrukcja historii myśli politycznej pozbawiona własnej pozycji polityczno-filozoficznej jest nieokreślona i dlatego nie stanowi Źródła wiedzy, b) bez przyjrzenia się historii myśli politycznej filozofia polityczna jest ślepa, wyobcowana, nieuzasadniona teoretycznie, a tym samym nawet potencjalnie niebezpieczna. Z metodologicznego punktu widzenia w artykule podjęto próbę ponownego ujęcia niektórych wniosków z rozważań na temat związku obu dyscyplin, ze szczególnym uwzględnieniem kontekstu francuskiego i angielskiego (a konkretnie dzieł Rosanvallona i Skinnera).
Skinner i Rosanvallon: pojednanie historii myśli politycznej i filozofii politycznej
Keywords: history of political thought; political philosophy; Skinner; Rosanvallon; Cambridge-school; historia myśli politycznej; filozofia polityczna; Rosanvallon; Skinner; szkoła Cambridge